(untitled) - Blonna, Richard (Boston, 2005)
Practical, thorough, and student-friendly, this text empowers readers to take control of their lives by recognizing stressors and implementing effective strategies to combat them.
Keywords: Stress (Psychology),Stress management,Căng thẳng (tâm lý),Quản lý căng thẳng